SOCIAL ORGANIZATION AND COMMUNITY COHESION IN XO-DANG EPIC - Lê Ngọc Bính (Tạp chí Khoa học Đại học Đà Lạt)
The Xo-Dang epic contains a lot of content such as history, society, culture, etc of the Xo-Dang people. This article will highlight the social organization characteristics and solid community cohesion reflected in the epics of this ethnic group.